2020
DOI: 10.3390/ijms21218009
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Axonal Outgrowth via Exogenous Low Forces

Abstract: Neurons are mechanosensitive cells. The role of mechanical force in the process of neurite initiation, elongation and sprouting; nerve fasciculation; and neuron maturation continues to attract considerable interest among scientists. Force is an endogenous signal that stimulates all these processes in vivo. The axon is able to sense force, generate force and, ultimately, transduce the force in a signal for growth. This opens up fascinating scenarios. How are forces generated and sensed in vivo? Which molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 173 publications
0
10
0
Order By: Relevance
“…Neurons are mechanosensitive cells, and the application of extremely low force positively modulate axonal elongation, neurite branching, and neuron maturation [5,[58][59][60][61][62][63][64][65]. Many studies demonstrated that magnetic nanoparticles are an efficient tool for magnetizing axons, and the subsequent application of a magnetic field gradient can generate such extremely low forces that drive productive axonal outgrowth [5,6,56,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are mechanosensitive cells, and the application of extremely low force positively modulate axonal elongation, neurite branching, and neuron maturation [5,[58][59][60][61][62][63][64][65]. Many studies demonstrated that magnetic nanoparticles are an efficient tool for magnetizing axons, and the subsequent application of a magnetic field gradient can generate such extremely low forces that drive productive axonal outgrowth [5,6,56,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80] There is a large body of literature on these topics and the interested reader is referred to several recent reviews for more details. [6,13,72,81]…”
Section: Forces At the Axon Growth Cone And Synapsementioning
confidence: 99%
“…[395,396] In general, force is a potent stimulus for axonal growth, with the elongation rate being directly proportional to the magnitude of tension. [6,397] From a translation perspective, one immediate application of stretch growth is ex vivo development of elongated nerve conduits that are ready to transplant for peripheral nerve repair. [398] Interestingly, in models of cyclic low magnitude strain, it was shown that glial cells exhibited signs of inflammatory reactive gliosis, and neurons became vulnerable to apoptosis.…”
Section: Therapies and Engineering Solutions To Disease Stemmed From Neuromechanobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to adhesive molecules and chemical signals, the mechanical forces to which the growth cone is subjected determine the growth cone movements as well [ 16 , 17 ]. For example, some axons, such as the ones from Xenopus retinal ganglion cells, are guided from stiffer to softer surfaces, showing straight and fast movement in stiffer surfaces, turning when exposed to stiffness gradients, and showing slower movement accompanied by increased growth cone area in softer surfaces [ 18 ], most probably due to changes in point contacts and thus growth cone traction forces.…”
Section: Growth Cone: Leading the Waymentioning
confidence: 99%